THE INFLUENCE OF CLASS PARTICIPATION AND PARENTING STYLE ON THE ACADEMIC PERFORMANCE OF ACCOUNTING STUDENTS - Silalahi, Sondang Aida; Garini, Meti Ardhiyah; Sapriani, Utari Noor; Dewi, Vika Tri (Universitas Negeri Medan, 2020)
This study aims to determine the effect of class participation and parenting style on the academic achievement of accounting and accounting education students of the Faculty of Economics, the State University of Medan. One hundred forty-two respondents were generated from a total population of 229 students. Data analysis techniques include descriptive statistics followed by the multiple regression analysis. The results showed that: 1) The significant value of the class participation variable is 0.203 > 0.05; thus, the class participation hypothesis rejected, meaning that there was no influence between class participation on academic achievement. 2) The significant value of the parenting variable is 0.014 < 0.05, confirming the hypothesis that there is an influence between parenting parents on academic achievement. 3) A significant value of 0.032 <0.05, then according to the basis of decision making in the F test, it can be concluded that the hypothesis is accepted, indicating class participation and parenting style influence on accounting students' academic achievement. 4) From the results of the two independent variables, which are the dominant variables affecting academic achievement is the class participation variable evidenced by the highest regression coefficient, which is 0.203 compared to the regression coefficient of the other variables. Keywords: Parent Participation; Parenting Parents; Academic Achievement.